Self-adapted task allocation algorithm with complicated coalition in wireless sensor network - Wen-zhong GUO; Jin-shu SU; Cheng-yu CHEN; Guo-long CHEN (Tongxin xuebao)
Considering the real-time requirement and some specific limitations (e.g.insufficient computing resource,energy constraint,etc) in task scheduling of wireless sensor networks,different priorities were assigned to tasks according to their deadline,and an adaptive task allocation algorithm with complicated coalition was designed through analyzing historical information.Moreover,a discrete particle swarm optimization algorithm was designed via employing binary matrix coding form.The proposed optimization algorithm generates coalitions in parallel and then performs subtask allocation algorithm based on load and energy balance.Finally,the experimental results show that the proposed algorithm strikes a good balance between local solution and global exploration,and achieves a satisfactory result within a short period of time.